Population analysis of the javan green peafowl (Pavo muticus muticus Linnaeus 1758) in Baluran and Alas Purwo National Parks, East Java (Biodiversitas Journal of Biological Diversity, 2011)
Hernowo JB, Alikodra HS, Mardiastuti A, Kusmana C (2011) Population analysis of the javan green peafowl (Pavo muticus muticus Linnaeus 1758) in Baluran and Alas Purwo National Parks, East Java. Biodiversitas 12: 99-106. The javan green peafowl (Pavo muticus muticus) have high pressure to the population and the habitat. The distribution of the bird at Java Island is clumped randomly at several types in condition of fragmented and isolated habitat and it has small individual number every unit population. Baluran and Alas Purwo National Parks are one of distribution javan green peafowl; it was chosen for study on the population analysis. The research was aimed to gain data and information on demographic population of javan green peafowl. The individual number of the bird was countedby call count transect method and councentration count. The population demographic parameter (individual number, age structure and sex ratio) of javan green peafowl was analyzed. The result shown that individual number of the javan green peafowl at Baluran National Park (BNP) was 69.1 birds (in 2006) and 70.5 birds (in 2007) not much differ, but it compared with the observation in1995 approximately was 117.7 birds had significant different. The green peafowl population at BNP declined around 47.50% during 12 years. Meanwhile the population at Alas Purwo National Park (APNP) was 80.7 birds (in 2006) and 73.5 birds (in 2007), if compared to observation in 1998 only 43 birds and in 2006 was 80.0 birds, the population grow up 86.05% during 8 years. The age structure of population indicated that both population (BNP and APNP) tend to unbalance pyramidal, where adult birds more abundance than sub adult or juvenile. The birds sex ratio at both (APNP and BNP) indicated that the peafowl life in polygyny system 1 male: 4 female > 1 male: 2.5 female.
Keywords: population, javan green peafowl, Baluran, Alas Purwo